Perbuatan Melawan Hukum Yang Mengakibatkan Akta Jual Beli Batal Demi Hukum (Studi Kasus Putusan Mahkamah Agung Nomor 1615 K/PDT/2020) - Liwandi, Reynaldi; Lukman, F.X. Arsin (Universitas Batanghari Jambi, 2023)
In conducting the sale and purchase of land, material requirements must be met followed by formal requirements, namely the deed of sale and purchase is drawn up and signed by the parties before the Land Deed Making Officer. The deed of sale and purchase serves as evidence that a binding agreement and agreement have been made among the parties involved, confirming the transfer of land rights accompanied by the payment of the price, thereby making the recipient of the rights or the buyer the new holder of the rights. This study aims to examine a tort of transferring land rights without the knowledge of the landowner in the case of Supreme Court Decision Number 1615 K/Pdt/2020, and the transfer of land rights based on national land law. The research method used in this study is normative legal research. This study resulted in the conclusion that the legal considerations and the judge's decision in the Supreme Court Decision Number 1615 K/Pdt/2020 were appropriate, proving that the Defendants had engaged in a tort under Article 1365 of the Civil Code, which resulted in the transfer of ownership rights without the knowledge of the Plaintiff. Since the enactment of Government Regulation No. 10/1961, which was later amended to Government Regulation No. 24/1997 concerning Land Registration, the sale and purchase transactions are conducted in the presence of authorized Land Deed Officers who have the authority to create the deed. The conclusive evidence of a transfer of the rights from the seller to the buyer, along with the payment of the agreed-upon price, is established by the executed deed of sale and purchase between the involved parties. Therefore, the relevant sale and purchase transaction has been carried out in a tangible manner.